Life histories, blood revenge, and warfare in a tribal population. - Chagnon, N A (Science, 1988)
Blood revenge is one of the most commonly cited causes of violence and warfare in tribal societies, yet it is largely ignored in recent anthropological theories of primitive warfare. A theory of tribal violence is presented showing how homicide, revenge, kinship obligations, and warfare are linked and why reproductive variables must be included in explanations of tribal violence and warfare. Studies of the Yanomamö Indians of Amazonas during the past 23 years show that 44 percent of males estimated to be 25 or older have participated in the killing of someone, that approximately 30 percent of adult male dealths are due to violence, and that nearly 70 percent of all adults over an estimated 40 years of age have lost a close genetic relative due to violence. Demographic data indicate that men who have killed have more wives and offspring than men who have not killed.